Tissue characterization by T1 and T2 mapping cardiovascular magnetic resonance imaging to monitor myocardial inflammation in healing myocarditis. (8th March 2017) - Bohnen, S.; Radunski, U.K.; Lund, G.K.; Ojeda, F.; Looft, Y.; Senel, M.; Radziwolek, L.; Avanesov, M.; Tahir, E.; Stehning, C.; Schnackenburg, B.; Adam, G.; et al.
Abstract : Aims: Monitoring disease activity in myocarditis is important for tailored therapeutic strategies. This study evaluated the ability of T1 and T2 mapping cardiovascular magnetic resonance (CMR) to monitor the course of myocardial inflammation in healing myocarditis. Methods and Results: Forty-eight patients with strictly defined acute myocarditis underwent CMR at 1.5 T in the acute stage, at 3-months ( n  = 39), and at 12-months follow-up (FU) ( n  = 21). Normal values were obtained in a control group of 27 healthy subjects. The CMR protocol included standard ('Lake-Louise') sequences as well as T1 (modified Look-Locker inversion recovery sequence, MOLLI) and T2 (gradient- and spin-echo sequence, GraSE) mapping. T1, T2, and extracellular volume (ECV) maps were generated using an OsiriX plug-in. Native myocardial T1, T2, and ECV values were increased in the acute stage, but declined with healing of myocarditis. The performances of global native T1 and T2 to differentiate acute from healed myocarditis stages were significantly better compared with all other global CMR parameters with AUCs of 0.85 (95% CI, 0.76–0.94) and 0.83 (95% CI, 0.73–0.93). Furthermore, regional native T1 and T2 in myocarditis lesions provided AUCs of 0.97 (95% CI, 0.93–1.02) and 0.93 (95% CI, 0.85–1.01), which were significantly superior to any other global or regional CMR parameter. Conclusion: Healing of myocarditis can be monitored by native myocardial T1 and T2 measurements without the need for contrast media. Both native myocardial T1 and T2 provide an excellent performance for assessing the stage of myocarditis by CMR.